Factors influencing the social acceptance of brain-computer interface technology among Chinese general public: an exploratory study - Xia, RuiTong; Yang, Shusheng (Frontiers in Human Neuroscience, 2024)
This study investigates the impact of social factors on public acceptance of Brain-Computer Interface (BCI) technology within China's general population. As BCI emerges as a pivotal advancement in artificial intelligence and a cornerstone of Industry 5.0, understanding its societal reception is crucial.Utilizing data from the Psychological and Behavioral Study of Chinese Residents (N=1923), this research examines the roles of learning ability, age, health, social support, and socioeconomic status in BCI acceptance, alongside considerations of gender and the level of monthly household income.Multiple regression analysis via STATA-MP18 reveals that while health, socioeconomic status, social support, and learning ability significantly positively correlate with acceptance, and age presents an inverse relationship, gender and household income do not demonstrate a significant effect.Notably, the prominence of learning ability and social support as principal factors suggests targeted avenues for increasing BCI technology adoption. These findings refine the current understanding of technology acceptance and offer actionable insights for BCI policy and practical applications.